Symbolic Meaning of Space: Interpreting Cosmological Order in Indigenous Balinese and Javanese Architecture - Pitana, Titis Srimuda; Anjar Sari, Pratiwi (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
Studies on Nusantara architecture often isolate spatial systems and disregard their shared cosmological foundations. This comparative study examines how cosmology shapes spatial planning in the Balinese Tri Mandala (a tripartite spatial hierarchy) and the Javanese Catur Gatra Tunggal (a quadripartite civic order), with a focus on orientation, zoning, and structure. Using an interpretive qualitative approach, the research draws on Gadamer’s philosophical hermeneutics, Ricoeur’s symbolic hermeneutics, and spatial phenomenology. The findings show that both traditions project cosmology into space through different spatial logics: Bali emphasizes a vertical sacred–profane hierarchy, whereas Java stresses horizontal integration of social, religious, and political domains. Variations in spatial form do not indicate distinct cosmological paradigms but rather different symbolic expressions of comparable ontological concepts. The novelty of this study lies in synthesizing zoning, structure, orientation, and philosophical meaning into a unified analytical model that views architecture as a spatial knowledge system mediating relationships among humans, nature, and transcendence.
Keywords: architectural cosmology; tri mandala; catur gatra tunggal; spatial hermeneutics; traditional spatial symbolism